Court Authority when a Claim of Invalidity of Registered Real Estate Transactions is proven: Analytical Study in Accordance with the Provisions of Article (13) From the Jordanian Real Property Law and its Amendments No. (13) Of 2019 - Alnatsheh, Abed Aljawad Daoud; Abu sulieh, Balqees Talal (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: To explore the options available to the trial court regarding invalid real estate transactions as stipulated in Article (13) of the Real Estate Ownership Law. Methods: A descriptive and analytical approach was followed by presenting and analyzing the text of Article (13) of the Real Estate Ownership Law, as well as some related provisions of the Jordanian Civil Code. The study also examined and analyzed some judicial decisions of the Jordanian Court of Cassation to determine their consistency. Results: The legislator aimed to maintain the stability of transactions and property ownership by introducing solutions that consider the negative effects of invalidating real estate transactions, while also balancing the rights of the involved parties. Conclusion: The Jordanian legislator deviated from the general rules stipulated in the Civil Code regarding invalidity and prescription by granting the court powers to either declare the transaction invalid or award compensation based on the case presented, within specific constraints.